2013
DOI: 10.1073/pnas.1320886110
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing evolutionary fitness in Plasmodium falciparum for drug discovery and suppressing resistance

Abstract: Drug resistance emerges in an ecological context where fitness costs restrict the diversity of escape pathways. These pathways are targets for drug discovery, and here we demonstrate that we can identify small-molecule inhibitors that differentially target resistant parasites. Combining wild-type and mutant-type inhibitors may prevent the emergence of competitively viable resistance. We tested this hypothesis with a clinically derived chloroquine-resistant (CQ r ) malaria parasite and with parasites derived by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 31 publications
1
52
0
1
Order By: Relevance
“…Using the 106/1 76I line, QN single-step selection experiments generated lines with an additional PfCRT Q352K or Q352R mutation that had acquired QN resistance but simultaneously regained CQ susceptibility (20). Separately, in vitro selection for resistance to the IDI-3783 compound that is selectively active against CQR parasites resulted in acquisition of the Q352R mutation in PfCRT (and concomitantly, a loss of CQR), thus providing a conceptual framework for the development of combination therapies that would exploit this evolutionary trap (21). These mutations occur in pfcrt exon 10, which corresponds to amino acid substitutions in transmembrane domain 9.…”
Section: Discussionmentioning
confidence: 99%
“…Using the 106/1 76I line, QN single-step selection experiments generated lines with an additional PfCRT Q352K or Q352R mutation that had acquired QN resistance but simultaneously regained CQ susceptibility (20). Separately, in vitro selection for resistance to the IDI-3783 compound that is selectively active against CQR parasites resulted in acquisition of the Q352R mutation in PfCRT (and concomitantly, a loss of CQR), thus providing a conceptual framework for the development of combination therapies that would exploit this evolutionary trap (21). These mutations occur in pfcrt exon 10, which corresponds to amino acid substitutions in transmembrane domain 9.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to reducing the risk of resistance to DSM265 emerging would be to pair this compound with another agent that has a similar pharmacokinetic profile and against which resistance would require a separate set of parasite mutations, thus decreasing the probability of dual drug resistance 108 . A complementary approach could be to pre-emptively block DSM265-resistance pathways by choosing as a partner another DHODH inhibitor against which DSM265-resistant parasites would be hypersensitive 109 . A similar phenomenon, whereby resistance to one class of inhibitors causes the mutated target to become hypersensitive to another inhibitor, has also been described for some PfATP4 mutants 110 .…”
Section: Next-generation Antimalarialsmentioning
confidence: 99%
“…Regarding the latter, an interesting approach has been the design of CQ-like compounds that couple targeting heme with a chemosensitizing component that counteracts mutant PfCRT-mediated CQ resistance 134,135 . Another strategy is to combine drugs that generate opposing selection pressures on the same target, as illustrated above with the example of DHODH, in which case a gain of resistance to one inhibitor can cause parasite hypersensitivity to another 109 . As mentioned in Box 1, detailed knowledge about PfCRT and PfMDR1 has shown that certain mutations conferring resistance to one drug can sensitize parasites to other agents, and has laid the theoretical groundwork for clinical trials (NCT02612545 and NCT02453308) with the triple ACTs AL plus AQ or DHA-PPQ plus mefloquine to test whether these combinations can successfully eliminate resistant and sensitive infections, and, potentially, block the emergence of parasites resistant to all three agents.…”
Section: Can We Design Drugs That Are ‘Resistance Proof’?mentioning
confidence: 99%
“…To circumvent the emergence of drug resistance, specific genomic loci can be identified (e.g., dhodh and pfcrt [Lukens et al 2014]) that exist in two alternate allelic states (Fig. 3).…”
Section: Intervention Impact Assessmentmentioning
confidence: 99%